Pengaruh Debt To Equity Ratio (DER) Dan Total Asset Turnover (TATO) Terhadap Net Profit Margin Pada PT Mustika Ratu Tbk Tahun 2015-2024 - Rahma Wati, Siti; Widodo, Adji (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This study aims to analyze the influence of the Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) on the Net Profit Margin (NPM) of PT Mustika Ratu Tbk during the 2015–2024 period. The results show that both DER and TATO have no significant effect on NPM, either partially or simultaneously. This is supported by the t-values of DER (1.001) and TATO (-0.686), which are lower than the t-table value (2.365), and the F-value (2.058), which is also lower than the F-table value (19.35). The coefficient of determination is 48.1%, indicating the contribution of DER and TATO to NPM. These findings highlight the importance of effective capital structure management and asset efficiency in improving company profitability Keywords: Debt to Equity Ratio, Total Asset Turnover, Net Profit Margin, The coefficient of determination (R²)